Analysis Potential Business Kebab Vegetable as Product Food Healthy for Creative Food Business Education - Nisri Ina Zahrah (INSPIRETECH GLOBAL INSIGHT, 2026)
Purpose of the study: Inadequate fruit and vegetable consumption remains a major public health concern in Indonesia, with only 3.3% of the population meeting the recommended intake of ≥5 servings per day. This condition highlights the need for innovative, fiber-based food products that can increase public interest in healthy eating. Integrating entrepreneurship education into nutrition programs provides an opportunity to develop nutritious and commercially viable food products, such as vegetable kebabs. Materials and methods: This study employed a descriptive quantitative approach using secondary data from a healthy food bazaar conducted by undergraduate nutrition students at the Faculty of Health Sciences, Bina Bangsa University, in April 2024. Business feasibility was assessed using Revenue–Cost (R/C) ratio analysis, while strategic positioning was evaluated through SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis, including IFAS and EFAS matrix assessments. Results: The total production cost for 30 vegetable kebabs per day was IDR 227,200, with total revenue of IDR 300,000 and a net profit of IDR 72,800. The R/C ratio was 1.32, indicating that the business is financially feasible (R/C > 1). SWOT analysis showed a strong internal factor score (2.24) and external factor score (2.01), positioning the business in Quadrant I (growth-oriented strategy). Key strengths included strategic location, affordable pricing, and guaranteed product quality, while opportunities were supported by digital promotion and increasing health awareness among students. Conclusions: The vegetable kebab business demonstrates strong financial feasibility and strategic growth potential. As an entrepreneurship-based educational initiative, this product provides practical learning experience for nutrition students while contributing to the development of healthy, innovative food businesses. Continuous product innovation and strategic marketing are essential to sustain and expand the business.